THE IMPLEMENTATION OF KHIYAR SYARAT ON TRANSACTION OF SHOES BY DROPSHIP SYSTEM IN THE CITY OF BANDA ACEH (A Study Case of Dropshipper in Syiah Kuala Sub-District) - Ade Nidya Fernanda; Muhammad Siddiq Armia; Rispalman Risfalman (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2021)
Dropshipping is a form of online buying and selling in which business actors act as intermediaries between genuine sellers (suppliers) and consumers. Shoe dropshippers in Syiah Kuala District do not stock goods and do not take care of shipments so they do not know the actual condition of the goods. Sometimes in online buying and selling like this there is a risk in the form of defects/damage to goods, shipping errors, etc. so a warranty system is needed to protect both parties from loss or disputes at a later date. The problem in this research is what is the form of return guarantee in the sale and purchase agreement of shoes in Syiah Kuala District by dropship and how is the khiyār review of the terms of the return guarantee form of dropship shoe purchase. In this study the authors used a sociolegal approach with descriptive analysis research methods based on data obtained from interviews. The result of this research is the guarantee provided by the dropshipper in the Syiah Kuala District in the form of exchanging goods (returns) and a refund (refund) for 3x24 hours with certain terms and conditions. In the concept of fiqh muamalah, the return guarantee has relevance to the khiyār requirement, because the dropshipper provides an option for returns within a certain time in order to guarantee the willingness of the parties. The provision of 3 days is in accordance with the terms of the khiyār time according to the terms of the fuqaha. The difference lies in the form of guarantee provided, in khiyār the terms of sale and purchase can be canceled if there is consumer defect or dissatisfaction, while the return guarantee by most dropshippers only provides exchange of goods, which shows that the sale and purchase cannot be canceled.